Sub-Optimal Treatment of Bacterial Biofilms - Tianyan Song; Marylise Duperthuy; Sun Nyunt Wai (MDPI AG, 2016)
Bacterial biofilm is an emerging clinical problem recognized in the treatment of infectious diseases within the last two decades. The appearance of microbial biofilm in clinical settings is steadily increasing due to several reasons including the increased use of quality of life-improving artificial devices. In contrast to infections caused by planktonic bacteria that respond relatively well to standard antibiotic therapy, biofilm-forming bacteria tend to cause chronic infections whereby infections persist despite seemingly adequate antibiotic therapy. This review briefly describes the responses of biofilm matrix components and biofilm-associated bacteria towards sub-lethal concentrations of antimicrobial agents, which may include the generation of genetic and phenotypic variabilities. Clinical implications of bacterial biofilms in relation to antibiotic treatments are also discussed.